The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/01000683rbcs20150568
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Correlation Between Physical Properties of Soil and Weeds in Two Management Systems

Abstract: The spatial correlation between soil properties and weeds is relevant in agronomic and environmental terms. The analysis of this correlation is crucial for the interpretation of its meaning, for influencing factors such as dispersal mechanisms, seed production and survival, and the range of influence of soil management techniques. This study aimed to evaluate the spatial correlation between the physical properties of soil and weeds in no-tillage (NT) and conventional tillage (CT) systems. The following physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…This factor is very important in semiarid regions, since rainfall is scarce and soils with higher water retention are fundamental for plant establishment and development. This hypothesis can be strengthened when taking into account the results of Schaffrath et al (2015), which found a positive special correlation between weed biomass and soil microporosity in an agricultural field in Paraná state under a conventional soil management system using a cross-semivariogram. This is because soils with higher microporosity generally have higher clay content and, consequently, higher water retention.…”
Section: An Acad Brasmentioning
confidence: 99%
“…This factor is very important in semiarid regions, since rainfall is scarce and soils with higher water retention are fundamental for plant establishment and development. This hypothesis can be strengthened when taking into account the results of Schaffrath et al (2015), which found a positive special correlation between weed biomass and soil microporosity in an agricultural field in Paraná state under a conventional soil management system using a cross-semivariogram. This is because soils with higher microporosity generally have higher clay content and, consequently, higher water retention.…”
Section: An Acad Brasmentioning
confidence: 99%